2016
DOI: 10.18632/oncotarget.14224
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine (CAM) in cancer patients: An Italian multicenter survey

Abstract: IntroductionComplementary and Alternative Medicine (CAM) include a wide range of products (herbs, vitamins, minerals, and probiotics) and medical practices, developed outside of the mainstream Western medicine. Patients with cancer are more likely to resort to CAM first or then in their disease history; the potential side effects as well as the costs of such practices are largely underestimated.Patients and methodWe conducted a descriptive survey in five Italian hospitals involving 468 patients with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 36 publications
7
83
2
1
Order By: Relevance
“…As outlined above, several foods are naturally rich in resveratrol, like nuts, grapes, apples, red fruits, black olives, capers, brown or red rice and others [89]. Notably, they are very common in the Mediterranean diet which has demonstrated to have significant anti-inflammatory, anti-obesity and cardioprotective properties [90]. Being an extremely reactive molecule as well as capable to interact both with cytoplasmic and nuclear proteins [89,90] in human cells, resveratrol has been studied over the years as complementary and alternative medicine (CAM) for the therapy of cardiovascular diseases like myocardial ischemia [90,91], myocarditis [92], cardiac hypertrophy and heart failure [93,94].…”
Section: Resveratrol In Cardio-oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined above, several foods are naturally rich in resveratrol, like nuts, grapes, apples, red fruits, black olives, capers, brown or red rice and others [89]. Notably, they are very common in the Mediterranean diet which has demonstrated to have significant anti-inflammatory, anti-obesity and cardioprotective properties [90]. Being an extremely reactive molecule as well as capable to interact both with cytoplasmic and nuclear proteins [89,90] in human cells, resveratrol has been studied over the years as complementary and alternative medicine (CAM) for the therapy of cardiovascular diseases like myocardial ischemia [90,91], myocarditis [92], cardiac hypertrophy and heart failure [93,94].…”
Section: Resveratrol In Cardio-oncologymentioning
confidence: 99%
“…Notably, they are very common in the Mediterranean diet which has demonstrated to have significant anti-inflammatory, anti-obesity and cardioprotective properties [90]. Being an extremely reactive molecule as well as capable to interact both with cytoplasmic and nuclear proteins [89,90] in human cells, resveratrol has been studied over the years as complementary and alternative medicine (CAM) for the therapy of cardiovascular diseases like myocardial ischemia [90,91], myocarditis [92], cardiac hypertrophy and heart failure [93,94]. The main mechanisms underlying its beneficial effects are based on its anti-oxidative and anti-inflammatory properties [89] as well as its improvements of calcium homeostasis in cardiomyocytes and reduction of cardiac fibrosis [95].…”
Section: Resveratrol In Cardio-oncologymentioning
confidence: 99%
“…Some limitations, however, also need to be considered. The primary weakness of our study was the lack of data on complementary and alternative medicines reported to be used by a considerable proportion of patients with cancer, as well as over‐the‐counter medication, which is also frequently used . Another limitation was the lack of data on the reasons for discontinuation of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The primary weakness of our study was the lack of data on complementary and TA B L E 2 Drug classes initiated among epithelial ovarian cancer patients between 3 months before and 6 months after the diagnosis, corresponding to the period of highest incidence rate of new drug treatment. The alternative medicines reported to be used by a considerable proportion of patients with cancer, [11][12][13] as well as over-the-counter medication, which is also frequently used. 14,15 Another limitation was the lack of data on the reasons for discontinuation of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the well-established anti-inflammatory activity of nutraceuticals (Berretta et al, 2017), we investigated about putative inhibitory effects of BA in the production of IL-8, IL-6, VEGF, MMP-9, and CXCL-12 in glioblastoma cells under proinflammatory conditions. First of all, incubation of cancer cells with LPS determines a significant stimulation of all analyzed interleukins and growth factors compared with the untreated one ( Figure 9).…”
Section: Ba Inhibits the Production Of Proinflammatory Interleukinsmentioning
confidence: 99%